Planificación como orientadora del proceso educativo y su incidencia en el aprendizaje del idioma inglés en los estudiantes del ii año de bachillerato de la unidad Educativa Prócer José de antepara del cantón Vinces, Provincia de los Ríos - Huacón Coello., Gianella Cecilia (2017)
The planning is a fundamental tool that the teacher uses on having given and to prepare a class, this tool allows him to organize and to guide the class of a precise and clear way. The planning performs vital importance so much for teachers as students since it allows to develop it of skills and skills in the area of study The planning helps to know how the class must be structured and this allows that the topics that are going to treat in the subject should be those of major impact, importance and indispensable to develop the knowledge of the students this by means of the receipt of clear ideas, veracious information and especially with activities that consolidate the learned. The teacher must have as aim help the students to develop his own ideas as for specific topics. The planning is the method by means of which it manages to define the aims of the class allowing hereby that the area of study should be dynamic and productive to the moment to give new knowledge to the students, the low performance not always takes place for the lack or few intelligence of the students but also for the bad educational habits of the teacher. The raised offer seeks to improve the planned activities implanting didactic activities and of easy development but especially that help the students to put into practice the learned and especially to use the planning as a technology that allows to implement new modalities of study benefiting to the whole educational community since student seeks to improve communication between dicente-, allowing to look for the best way of filling the emptinesses of knowledge of the students could have.